TINJAUAN KEWENANGAN PENJABAT KEPALA DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 10 TAHUN 2016 TENTANG PERUBAHAN KEDUA ATAS UNDANG-UNDANG NOMOR 1 TAHUN 2015 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2014 TENTANG PEMILIHAN GUBERNUR,BUPATI, DAN WALIKOTA MENJADI UNDANG-UNDANG - Nurhazlina Afia; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The 1945 Constitution does not explicitly emphasize the direct filling ofpositions for the process of filling the positions of Regional Heads in the regions,The existence of simultaneous Regional Head Election Preparations is a mandatefrom Law Number 7 of 2017 and Law Number 10 of 2016, has an impact onleadership in area Be it governors, regents or mayors related to the term of office.Replacement of leadership in the regions before the end of the regional head'sterm of office is based on statutory regulations where regional heads who aredemocratically elected can be replaced by Acting (Pj) Regional Heads. ) Districthead. As for the issues to be discussed are: 1) What is the authority of the Acting(Pj) regional head in the perspective of laws and regulations? 2) What is the idealconcept of the authority of the Acting (Pj) regional head in administering theGovernment. The type of research used in this legal research is normative legalresearch. Conceptual Approach). Number 1 of 2014 Concerning the Election ofGovernors, Regents and Mayors Becomes Law. Article 201 paragraphs (10) and(11), resulting in the extent of the Authority of the Acting Regional Head andunclear boundaries of authority. The two ideal concepts of the authority of theActing (Pj) regional head include: a) The Authority of the Acting Regional Headis regulated clearly and firmly in the Law -Acts on the grounds that the term ofoffice of Acting Regional Heads is sufficient, b) Implementation in establishingstrategic policies for Acting Regional Heads involves the Role of the DPRD, thisis very important related to the relationship of interests between the regionalgovernment and the Regional Representatives Council, c) There are rulesregarding Accountability of Acting Heads Region on the implementation ofAuthority, so that the content and time are clear responsibility for the authority ofthe Acting Regional Head.Keywords: Authority, Acting Regional Head, Act